Comparison analyses of five mean areal rainfall estimation methods in widely varying years - Pizarro T., Roberto; Ramírez B., Claudio; Flores V., Juan Pablo (Bosque (Valdivia), 2003)
This study approaches the problems of mean areal rainfall estimation in three longitudinal sectors of the VII Region of Chile: the Andes mountain range, the central valley, and coastal mountain range. The methods used were the Mean Arithmetic (MA), Thiessen’s Polygons (Th), Isohyets (Iso), Modified Thiessen (ThM) and Inverse Squared Distance (IDC). These methods were applied to two extreme series of pluvial data, dry (A.S.) and wet years (A.H.). An analysis and comparison of the methods recommended the application of any of the five methods for the central valley, but considered the MA method best due to its simplicity. A similar situation was found for the coastal mountain range, except the ThM. In the case of the Andes mountain chain, the only method not recommended was the IDC.